Effect Of Servant Leadership On Employees’ Empowerment, Knowledge Sharing And Creativity In Al-Masjid Al-Haram And Al-Masjid Al-Nabawi - Ali M, Alasmari Saad (2020)
Every year, The “General Presidency of Al-Masjid Al-Haram and Al-Masjid Al-Nabawi” organization in Saudi Arabia serves millions of visitors to perform Umrah and Hajj. With reference to this organization, its employees need to be more creative and demonstrate a good relationship with their leaders to provide quality and efficient services and ensure high satisfaction levels among local and international Hajj and Umrah pilgrims. This study aims to examine the relevance of servant leadership in the organization and how the different dimensions of servant leadership enhance the employees’ creativity. In addition, the study investigates the mediating effect of employees’ empowerment on the relationship between servant leadership dimensions and employees’ creativity and, the moderating role of knowledge sharing on the relationship between employees’ empowerment and employees’ creativity.